Reliability, validity and usefulness of a new response time test for agility-based sports: A simple vs. complex motor task - Pojskic, H.; Pagaduan, J.; Uzicanin, E.; Separovic, V.; Spasic, M.; Foretic, N.; Sekulic, D. (Journal of Sports Science & Medicine, 2019)
The importance of response time (RT) in sports is well known, but there is an evident lack of reliable and valid sport-specific measurement tools applicable in the evaluation of RT in trained athletes. This study aimed to identify the validity, reliability, and usefulness of four newly developed RT testing protocols among athletes from agility-saturated (AG) and non-agility-saturated (NAG) sports. Thirty-seven AG and ten NAG athletes (age: 20.9 ± 2.9; eleven females) volunteered to undergo: three randomized simple response time (SRT-1, SRT-2, and SRT-3) protocols that included a single limb movement, and one complex response time (CRT) protocol that included multi joint movements and whole body transition over a short distance (1.5 and 1.8m). Each RT test involved 3 trials with 5 randomized attempts per trial. Two sensors were placed at the left- and right-hand side for SRT-1 and SRT-2. Three sensors were positioned (left, middle, right) in SRT-3 and CRT. The intra-class-correlation coefficient (ICC) was calculated as a measure of reliability. Independent sample t-test, effect size (d), and area-under-the-curve (AUC) were calculated to define discriminative validity of the tests. The results showed the newly developed tests were more reliable and useful in the AG than NAG athletes (i.e., ICC between 0.68 and 0.97 versus 0.31-0.90, respectively). The RT of AG athletes was faster than that of NAG athletes in the CRT test from the left (p <0.01, d = 2.40, AUC: 0.98), centre (p < 0.01, d = 1.57, AUC: 0.89), and right sensor (p < 0.01, d = 1.93, AUC: 0.89) locations. In contrast, there were no differences between the groups in the SRT tests. The weak correlation (i.e., r= 0.00-0.33) between the SRT and CRT tests suggests that response time of the single limb and multijoint limb movements should not be considered as a single motor capacity. In conclusion, this study showed that AG athletes had faster response time than their NAG peers during complex motor tasks. Such enhanced ability to rapidly and accurately reprogram complex motor tasks can be considered one of the essential qualities required for advanced performance in agility-based sports. Key Points